Neoplasmas mamários e níveis de cálcio e magnésio em fêmeas caninas - Pereira, Isabel Cristina (2012)
The longevity of dogs has increased the number of neoplasm cases, and the breast neoplasm is one of the most frequent diagnosed in this species. The female dogs are important as a study population as they present similarities between the breast neoplasms developed in humans and canines, thus allowing the use of the compared pathology in an attempt to have a better understanding of the disease. Changes in calcium and magnesium levels may be related to the presence and occurrence of breast neoplasms, but there is no defined standardization of these changes. The study aimed to analyze epidemiological data in canine patients with breast neoplasms, determine levels of serum calcium and magnesium in dogs with breast neoplasms before and after excision, and associate variation of calcium and magnesium blood levels with the neoplasms malignity. The study had a sample of 53 females 53 female dogs with tumors in the mammary gland, from which we obtained data of descriptive characteristics of the sample, regarding the review of the animal, exposure to risk factors and tumor development, associated with the morphological characteristics and anatomical location. Excision of tumor masses was performed for histopathological analysis evaluating the surgical margin and classifying the patients according to the biological behavior and malignancy degree: high malignancy (HM), intermediate malignancy (IM), low malignancy (LM) and benign (B). In further study, there was a loss of 17 dogs in the study for the analysis of mineral levels the period of 180 days and analyzed 36 dogs with mammary neoplasms and 28 healthy dogs without breast tumors were studied as controls. Dogs were evaluated on day zero (before surgery) in regard to assessments of tumor mass, and on that date, surgery was carried out in order to send the tumoral part for anatomopathologic evaluation taking into account the classification in biological behavior. Serum calcium and magnesium dosage (absorbance spectrophotometry) was performed prior to the excision of tumors (on day zero) and at 60 and 180 days after surgery, and at the same time interval the serum levels of minerals in the control group were evaluated. Of the 53 dogs studied, 24 showed high malignant tumors, 12 intermediate malignant tumors, 13 low malignancy tumors and four benign tumors. The elderly patients were the most frequent ones in the malignancy group. There was no relationship between biological behavior when compared to: age range, size, breed, time of onset and development, previous ovariohysterectomy and the use of contraceptives. As for location, of the 171 breasts affected, the development of neoplasms of greater malignancy occurred in medial abdominal and inguinal mammary glands. It was demonstrated the relationship between margin involvement and development of pulmonary metastasis. The neoplasic mobility and consistency were identified as prognostic factors for dogs with mammary neoplasms, while the other variables studied were not related to prognosis, while the other studied variables were not related with the prognosis. Data concerning the 36 females suffering from canine mammary neoplasms, which were observed, 13 had tumors of high malignancy (HM), nine of intermediate malignancy (IM), 10 of low malignancy (LM) and four benign (B). The average of calcium levels in the control group was 10.07 mg / dl and magnesium of 2.04 mg / dl. Mean levels of calcium serum of patients in group LM and IM were respectively 8.63 mg / dl and 8.77 mg / dl, both differing statistically (p <0.001) from the control group. The patients in the HM group had a mean calcium of 12.00 mg / dl and differed significantly (p <0.001) from the mean levels obtained in the control group. Regarding the serum levels of magnesium, it was demonstrated statistical difference between the control group (2.04 mg / dl) and the LM groups (p <0.001), IM groups (p = 0.002) and HM groups (p <0.001), with averages of 57 mg / dl, 1.67 mg / dl and 2.56 mg / dl, respectively. Both in the serum levels of calcium and magnesium no statistical differences between control group and group L were shown. It was observed that in animals with mammary neoplasms, the blood values of the studied minerals differed between the first and last collection in the LM groups (p = 0.0125) and HM groups (p = 0,0,0087) in the levels of calcium and in the same LM groups (p = 0.0124) and MA (p = 0.0015) in the levels of magnesium. The results showed that neoplasm mobility and consistency were correlated with malignancy and worse prognosis of the patient, and a strong relationship between margin involvement and lung metastases. Also, dogs with tumors of low malignancy and intermediate malignancy have hypocalcemia and hypomagnesemia, as well as in the cases of malignant neoplasms there is high hypercalcemia and hypermagnesemia, both going back to the physiological levels after six months of surgical excision